Influence of Key Environmental Conditions on Microbially Induced Cementation for Soil Stabilization - Cheng, Liang; Shahin, Mohamed; Mujah, Donovan (American Society of Civil Engineers, 2017)
Microbially induced calcite precipitation (MICP) is a sustainable biological ground improvement technique that is capable of altering and improving soil mechanical and geotechnical engineering properties. In this paper, laboratory column studies were used to examine the effects of some key environmental parameters on ureolytic MICP mediated soils, including the impact of urease concentrations, temperature, rainwater flushing, oil contamination, and freeze–thaw cycling. The results indicate that an effective crystal precipitation pattern can be obtained at low urease activity and ambient temperature, resulting in high improvement in soil unconfined compressive strength (UCS). The microstructural images of such crystals showed agglomerated large clusters filling the gaps between the soil grains, leading to effective crystals formation. The rainwater flushing was detrimental to the biocementation process. The results also indicate that traditional MICP treatment by the two-phase injection method did not succeed in treatment of oil-contaminated soils, and the proposed premixing of bioflocs with soil can significantly improve UCS and stiffness of oil-contaminated soils. Finally, MICP-treated soils showed a high durability to the freeze–thaw erosion, which is attributed to the interparticle contact points and bridging of crystals formation.